Proliferating Cell Nuclear Antigen is a novel inhibitory ligand for the natural cytotoxicity receptor NKp44 - Rosental, Benyamin (2011)
Natural Killer (NK) cells play an important role in the early immune response to cancer. The NKp44 activating receptor is the only Natural Cytotoxicity Receptor that is expressed exclusively by primate NK cells; yet, its cellular ligands remain largely unknown. Proliferating Cell Nuclear Antigen (PCNA) is overexpressed in cancer cells. We show that the NKp44 receptor recognizes PCNA. Their interaction inhibits NK cell function through the NKp44-Immunoreceptor Tyrosine-based Inhibitory Motif (ITIM). The physical interaction of NKp44 and PCNA is enabled by recruitment of target cell PCNA to the NK immunological synapse. We demonstrate that PCNA promotes cancer survival by immune evasion through inhibition of NKp44-mediated NK cell attack.